2021
DOI: 10.3389/fped.2021.802214
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of Inflammation-Related Markers and Thyroid Function in Pediatric Thyroid Cancer Patients

Abstract: Few researchers have studied the diagnostic value of inflammation-related hematological indexes of pediatric thyroid carcinoma exclusively. Whether thyroid-stimulating hormone (TSH) is an independent risk factor for pediatric thyroid cancer is still controversial. To assess the correlativity and predictive values of inflammation-related markers and thyroid function in pediatric thyroid cancer patients, we collected a total of 270 children with thyroid nodules for two consecutive years. Clinical data including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been established that elevated NLR is associated with malignant pathological findings in a variety of solid tumors (prostate, endometrial, adrenal, lung, and thyroid cancers) ( 28 32 ), including, of course, renal tumors ( 33 , 34 ). In addition, studies have also confirmed the association of NLR with prognosis in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that elevated NLR is associated with malignant pathological findings in a variety of solid tumors (prostate, endometrial, adrenal, lung, and thyroid cancers) ( 28 32 ), including, of course, renal tumors ( 33 , 34 ). In addition, studies have also confirmed the association of NLR with prognosis in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated its use as a reliable predictor of severity for diverse conditions, including sepsis, COVID 2019 (COVID-19), and acute pancreatitis ( 24 , 29 , 30 ). In oncology, the NLR has been studied in numerous malignancies as a diagnostic and prognostic tool ( 31 - 33 ). In recent years, several studies have explored the potential of NLR as a prognostic biomarker for advanced GC treated with immunotherapy, and the results vary.…”
Section: Introductionmentioning
confidence: 99%